Transient catalytic activity of calcined dolomitic limestone in a fluidized bed during gasification of woody biomass - Pohorely, M.; Jeremias, M.; Skoblia, S.; Beno, Z.; Syc, M.; Svoboda, K. (American Chemical Society, 2016)
Calcined dolomitic limestone mixed with silica sand in a fluidized bed can catalytically enhance the gasification of woody biomass. The lime is prone to attrition and carry over from the reactor and to deactivation caused by pore sintering; therefore, it has to be replenished continuously or periodically to maintain catalytic activity of the fluidized bed. The main aim of this paper was to explore the level of the decrease of the catalytic activity of the fluidized bed if the limestone is not replenished and to estimate a critical period for its top-up. Wood chips were gasified first in a silica sand fluidized bed (1080 g), to obtain background data without the catalytic effect of limestone. After 5 h of operation, dolomitic limestone (1050 g) was added to the fluidized bed and left to calcine. Its catalytic activity was monitored during the following 6 h. During the second part of the experiment, the yield of the main gases (H2, CO, CH4, CO2, and H2O) remained almost unchanged. The yield of minor organic gases and tars rose slightly but still remained far below the value attained with only silica sand. The heavy polyaromatic tar compounds were effectively decomposed during the first 3 h after the addition of dolomitic limestone. It was concluded that the catalytic activity of dolomitic lime remains in an acceptable level during the first 3 h after its addition into the fluidized bed, suggesting that periodic rather than continuous replenishment of limestone should be sufficient.